AN EVALUATION AND EMPIRICAL STUDY OF THE DISCLOSURE OF ACCOUNTING POLICIES IN PUBLISHED FINANCIAL STATEMENTS* - Rao, Kailas J. (Journal of Finance, 1975)
The following explanation of techniques is provided to help you understand markings or patterns which may appear on this reproduction.1.The sign or "target" for pages apparently lacking from the document photographed is "Missing Page(s)".If it was possible to obtain the missing page(s) or section, they are spliced into the film along with adjacent pages.This may have necessitated cutting thru an image and duplicating adjacent pages to insure you complete continuity.2. When an image on the film is obliterated with a large round black mark, it is an indication that the photographer suspected that the copy may have moved during exposure and thus cause a blurred image.You will find a good image of the page in the adjacent frame.3. When a map, drawing or chart, etc., was part of the material being photographed the photographer followed a definite method in "sectioning" the material.It is customary to begin photoing at the upper left hand corner of a large sheet and to continue photoing from left to right in equal sections with a small overlap.If necessary, sectioning is continued again -beginning below the first row and continuing on until complete.4. The majority of users indicate that the textual content is of greatest value, however, a somewhat higher quality reproduction could be made from "photographs" if essential to the understanding of the dissertation.